Difference in improved water source adoption between urban and rural households in Cameroon - Totouom, Armand (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2024)
Many households living in developing countries still collect water from unimproved sources. The situation is particularly worse in rural areas. This study analyses the differences in improved water source adoption between urban and rural households in Cameroon. Our analysis uses data from the fifth Cameroon Demographic and Health survey conducted in 2018-2019. Results from logit regressions suggest that the use of improved water source increases when the head of household is a woman. It also increases with education, access to information and wealth. Conversely, it decreases with household size. The approach of Fairlie (2006) is further used to evaluate the contribution of the above factors to urban-rural differences in the adoption of improved water sources. Our analysis shows that the above factors explain 41% of the differences in water source choices observed between urban and rural households. The policy recommendations of the research are described in the paper.